Exploring Nurse Dyads’ experiences of scope of practice in nursing homes: A qualitative descriptive study from the FLORENCE project - Ole Martin Nordaunet; Hanne Aagaard; Cecilia Olsson; Edith Roth Gjevjon; Gunilla Borglin (PLoS ONE, 2025)
Background A nurse’s scope of practice includes the full range of roles, functions, responsibilities, and decision-making authority. However, how this scope—particularly in relation to the fundamentals of care—is experienced by registered nurses and non-registered nurses in nursing homes remains underexplored. This study aimed to explore the experiences of nurses regarding their mutual general scope of practice, the differences in their individual scope of practice, and their respective scopes in relation to the fundamentals of care in the context of nursing homes. Methods This qualitative study included eight nursing dyads (n = 16) from four nursing homes in south-east Norway. Data were collected through individual, focused interviews, i.e., non-dyadic data, and analysed using the framework method for dyadic analysis. The study followed the Standards for Reporting Qualitative Research (SRQR). Results Registered nurses described emotional strain due to a gap between professional ideals and the realities of high-pressure, understaffed environments. The contrast between being perceived as “too posh to wash” and “too busy” highlighted how systemic factors, rather than personal attitudes, shaped role perceptions. These constraints influenced care delivery and undermined their professional identity. Registered nurses tended to focus on indirect care and physical needs, while non-registered nurses took on more direct care, particularly the fundamentals of care—physical, relational, and psychosocial. Although the registered nurses valued holistic care, frequent delegation to the non-registered nurses raised concerns about care quality and role clarity. Conclusion Registered nurses’ scope of practice was shaped more by workload demands than by reluctance to engage in the fundamentals of care. The dyadic approach provided new insights into how professional responsibilities and activities are co-constructed in complex care settings. Findings highlight the need for organisational and clinical strategies to clarify role boundaries, strengthen registered nurses’ professional identity, reinforce the delivery of the fundamentals of care, and support effective and safe delegation practices.